Pengaruh Media Kartu Kata Terhadap Kemampuan Membaca Permulaan Siswa Kelas 2 SD - Saputri, Tika; Ratnasari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Reading is a fundamental part of language proficiency, especially in Indonesian, which is the national language. Therefore, mastering early reading skills is a prerequisite for mastering other language skills. Finding out whether the use of word card media has an impact on students' reading skills is the purpose of this study. This study used a quasi-experimental research design. Reading assessment was used to collect data. The reliability of the instrument was tested with the split-half method, while its validity was based on content validity. It is recommended that teachers use card media to teach beginning reading in grade two elementary school because the use of word card media can affect students' beginning reading ability. The results showed that the significance value (2-tailed) was 0.05 in accordance with the two means difference test with t-test using SPSS software with a significance level of 0.05. Since the sig value is 0.05, H0 is rejected for the test of the average difference in the final score of students' beginning reading ability, especially between two parties. This indicates that there is a difference between students who use word card media and those who do not use word card media. Keywords: Students' Reading Ability, Word Card Media